My busy brain : a first look at ADHD - Thomas ,Pat; Keay, Claire (London Wayland, 2022)
This picture book explains what Attention Deficit Hyperactivity Disorder, or ADHD, is in simple terms. Its aim is to promote understanding and ongoing discussion with children who have ADHD or those who have siblings or classmates with it
Education
Keywords: Attention-deficit hyperactivity disorder; Picture books